2017
DOI: 10.1126/science.aag3009
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the human DC lineage through the integration of high-dimensional techniques

Abstract: Dendritic cells (DC) are professional antigen-presenting cells that orchestrate immune responses. The human DC population comprises two main functionally specialized lineages, whose origins and differentiation pathways remain incompletely defined. Here, we combine two high-dimensional technologies-single-cell messenger RNA sequencing (scmRNAseq) and cytometry by time-of-flight (CyTOF)-to identify human blood CD123CD33CD45RA DC precursors (pre-DC). Pre-DC share surface markers with plasmacytoid DC (pDC) but hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
563
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(612 citation statements)
references
References 76 publications
42
563
1
6
Order By: Relevance
“…(For interpretation of the references to color in this figure legend, the reader is referred to the Web version of this article.) population of pre-cDCs expressing AXL that highly expresses co-stimulatory molecules (See et al, 2017;Villani et al, 2017). Although it can be deduced from these studies that bona fide pDCs still outnumber contaminating cDCs using this gating strategy, it is not known whether the extent of pre-cDC contamination varies between males and females or whether it is affected by infection.…”
Section: Discussionmentioning
confidence: 68%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the Web version of this article.) population of pre-cDCs expressing AXL that highly expresses co-stimulatory molecules (See et al, 2017;Villani et al, 2017). Although it can be deduced from these studies that bona fide pDCs still outnumber contaminating cDCs using this gating strategy, it is not known whether the extent of pre-cDC contamination varies between males and females or whether it is affected by infection.…”
Section: Discussionmentioning
confidence: 68%
“…Our study identified a progenitor marked as CD34 -CD123 + cells in cord blood and in human dermis that gave rise primarily to the CD11c + CD1c + CD5 + DCs, which we referred to as "pre-CD5 + DCs." Pre-cDCs were initially found in humans within the CD34 -CD123 -fractions (28); however, a recent study reported the presence of CD123 hi CD33 + CD45RA + CD303 + pre-DCs in peripheral blood (47). In contrast with See et al, our gating strategy excluded all the cells that expressed the pDC marker CD303 / BDCA-2; thus, perhaps we looked at a distinct, possibly more committed, pre-cDC subset.…”
Section: Cd1cmentioning
confidence: 78%
“…This is in line with previous studies suggesting mixed myeloid and lymphoid origin of pDCs 29,[37][38][39][40] and could help to resolve this controversy. Hence, our study sheds light on the origin of pDCs in the bone marrow, adding another piece to the puzzle of pDC versus cDC differentiation, which is still subject of intense research 37,38,[41][42][43] . As another example, we note that FateID recovered a recently characterized bipotent progenitor of monocytes and neutrophils 3 ( Supplementary Fig.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Ismentioning
confidence: 86%